PSYCHOLOGICAL WELL-BEING AMONG UNIVERSITY STUDENTS: FACILITATORS AND OBSTACLES OF ACADEMIC PERFORMANCE - Martínez Martínez, Isabel Mª; Bresó Esteve, Edgar; Llorens Gumbau, Susana; Grau Gumbau, Rosa (Anales de Psicología / Annals of Psychology, 2005)
The quality of the service in the learning process is an important goal of Universities. In this way, the identification of obstacles and facilitators of the learning process, as well as its relationship with subjective well-being and performance of students is a key topic. Current research was done among 872 University students from Universitat Jaume I (Spain) from 18 different academic specialities of the three University centres. Results from self-report questionnaire and qualitative techniques (brainstorming and focus groups), showed a positive relationship among academic obstacles, burnout and intention to leave. On the other hand, academic facilitators are positively related with engagement, commitment, self-efficacy, satisfaction and happiness. Regarding academic performance, we found gain and loss spirals among past success/failure, subjective (un/)well being, and future success/failure. Finally, we proposed different intervention measures in order to reduce academic obstacles and optimise facilitators among students.